Mexico : Selected Issues. (IMF Staff Country Reports; Country Report ;, 2001)
This paper focuses on the Mexican economy, its output fluctuations, and analyzes the country's external competitiveness in the context of medium-term external current account sustainability. The study also presents different measures of the fiscal deficit, including the traditional budget balance, and reviews measures on the fiscal stance and fiscal impulse. It examines the evolving relationship between inflation and the exchange rate, using fixed and time-varying coefficient models. The paper describes the methodology, provides the rationale for estimating time-varying parameter models, and presents the estimation results.